Involvement's Barriers of Micro and Small Firms into EU Energy Transition - Tomasz Bernat; Aleksandra Gasior; Renata Lisowska; Katarzyna Szymanska; Razvan Zaharia (Amfiteatru Economic, 2023)
One of the greatest challenges for modern companies is finding a balance between achieving environmental goals and being competitive on the market. The current situation forces companies to overcome various challenges that contribute to reducing energy consumption. The aim of the article is to try to answer the following question: What problems can be identified for the smallest business entities in the implementation of environmental standards imposed by legislation? In search of an answer to this question, the structure of this article was assigned, in which the following was described: the main issues related to energy transformation in the EU, the SME sector was characterised against the background of the economy and energy challenges, the methodology, results, and results of the research conducted on Polish enterprises were presented. The research, based on a structured and standardized survey questionnaire, was conducted with the use of the CATI technique between April and May 2022 among owners of micro and small enterprises operating in Poland. As research has shown, there are various barriers that limit the participation of the surveyed companies in energy transformation.
Keywords: Q51; Q56; Q48; 330; micro and small firms; energy transition; barriers for companies; involvements of companies in energy transition process